STUDI PENGGUNAAN ALUMUNIUM FOIL DAN TEMBAGA SEBAGAI PERMUKAAN SOLAR DISTILLATION SYSTEM TERHADAP KUALITAS AIR GAMBUT - ghofur, abdul ghofur (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2022)
Distillation technology utilizes the separation of components of a material based on differences in their boiling points by utilizing heat energy. The purpose of this study was to find out which water was distilled between the distillation apparatus and the surface of aluminum foil or copper. The solar distillation system is made with a length of 60 cm and a width of 40 cm, with a clear glass cover with a thickness of 5 mm which forms an angle of 30º. This research is a comparison, which in this study compared the distilled water produced between the Solar distillation system with an aluminum foil surface and the Solar distillation system with a copper surface. Parameters to be analyzed are ambient temperature (Ta), distillation room temperature (Td), water temperature (Tw), and glass surface temperature (Tg) The results showed that the solar distillation system using a copper surface produced more distilled water than the aluminum foil surface, that is, water was distilled for one day, with 230 milliliters of copper, while 210 milliliters of aluminum foil.Keywords : solar distillation , aluminum foil , copper